Maxillary First Premolar with Three Roots and Three Root Canals: A Case Report - Singh, Vimmi; Jha, Gyanendra; Agrawal, Navin; Shrestha, Sushmita (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Maxillary first premolar is most commonly a bi-rooted tooth, occasionally having three roots. It usually has two canals, but may rarely have three, which can easily be missed, demanding more attention during endodontic intervention. This paper reports this rarity of 3 roots and 3 canals in maxillary first premolar, highlighting the difficulties and special care needed during endodontic treatment. Careful investigation in diagnostic radiograph by professionals along with proper root canal treatment following all the necessary steps in detecting and bringing the possible changes brings about the success of the treatment.